High-strength and high-toughness PET foam as well as raw material composition and preparation method thereof
By using special tensile elements and convergent runner technology during the preparation of PET foam, the dispersed phases in PET foam form high specific surface area fibers, which solves the problem of insufficient mechanical properties of PET foam and achieves high strength and high toughness PET fiber composite foam.
Patent Information
- Application Number
- CN202510007403.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The prior art is difficult to significantly improve the mechanical properties of PET foams, especially in terms of compression resistance and shear strength, and there are limited methods for introducing inorganic fillers or regulating the cell structure.
By designing special tensile elements to apply tensile stress to the dispersed phase in the PET on the twin-screw extruder, it becomes fibrous, and a convergent runner is designed within the extrusion die to increase the fiber aspect ratio, Uniform dispersion of fibers with high specific surface area.
The compression strength, shear strength and shear elongation of the PET foam are significantly improved, and high-strength and toughness PET fiber composite foam is prepared.
Smart Images

Figure CN119391151A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-strength and high-toughness PET foam and a raw material composition and a preparation method thereof, belonging to the technical field of polymer material preparation. Background Art
[0002] Polyethylene terephthalate (PET) foam has excellent properties such as high temperature dimensional stability, thermal insulation, and chemical resistance. Currently, PET foam has been widely used in industries such as construction, aerospace, modern automobiles, ships, and food packaging. The use of PET foam is conducive to reducing the use of fossil resources and protecting the environment. However, the development of engineering fields such as wind turbine blades and aerospace has put forward higher requirements on the mechanical properties of PET foam, such as foam compression resistance.
[0003] Generally, the mechanical properties of PET foam are improved by introducing inorganic fillers and regulating the pore structure. Although the introduction of inorganic fillers can improve the mechanical properties of PET foam, excessive introduction of inorganic fillers will lead to the formation of open-cell foam during the PET foaming process; at the same time, the regulation of the foam pore structure is limited at the same density. Therefore, these methods are unlikely to significantly improve the mechanical properties of PET foam.
[0004] The preparation of polymer fiber composites by in-situ fiberization technology in polymers is an effective method to improve the mechanical properties of polymers. The in-situ fiberization process refers to the process in which the blend with the initial island morphology is stretched in a molten (hot stretching) or frozen (cold stretching) state, and the spherical dispersed phase particles are deformed into a fiber structure by the shear and tensile forces acting on the blend. The fiber structure with a high specific surface area can play a role in crystallization nucleation to increase the crystallization rate of the polymer on the one hand, and can act as a bubble nucleating agent to reduce the pore structure on the other hand, and the fiber can enhance the stress transfer between the polymer matrix and the dispersed phase. Converting the island morphology of the dispersed phase of the blend into micron or nanofibers is a method that can significantly improve the rheological properties, crystallization properties and mechanical properties of the polymer blend system.
[0005] At present, it is very difficult to combine in-situ fiber technology with supercritical continuous extrusion foaming to prepare polymer fiber composite foam directly through one-step extrusion foaming. Generally, the polymer fiber composite is first prepared by in-situ fiberization technology and prepared into a masterbatch, and the fiber is introduced into the polymer foam through the masterbatch during the extrusion foaming process. However, this will lead to a decrease in fiber dispersion, weaken the crystallization nucleation, bubble nucleation and stress transfer effects of the fiber, and greatly increase production costs and reduce production efficiency. Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a PET foam and a raw material composition and a preparation method thereof, wherein the PET foam has the advantages of high strength and high toughness.
[0007] To achieve the above object, the present invention first provides a raw material composition of high-strength and high-toughness PET foam, wherein the raw material composition comprises, by weight: PET resin 100 parts; Dispersed phase 0.3~0.75 parts; Naphthalene hydroxycarboxylic acid-parahydroxybenzoic acid copolyester (PHBNA) less than 10 parts; Thermoplastic elastomer 10 parts or less.
[0008] In the above raw material composition, preferably, the dispersed phase is selected from one or a combination of two or more of 2,2'-(1,3-phenylene)-bisoxazoline (PBO), pyromellitic anhydride (PMDA) and triglycidyl isocyanurate (TGIC).
[0009] In the above raw material composition, preferably, the naphthylhydroxycarboxylic acid-parahydroxybenzoic acid copolyester is prepared by the following steps: Step 1: mixing p-hydroxybenzoic acid and acetic anhydride in a molar ratio of 1:1 to 1:6 (more preferably 1:2), adding a catalyst, and then heating and reacting under a nitrogen environment; after the reaction is completed, precipitating a crystal, washing, and drying to obtain a first product; Step 2: 6-hydroxy-2-naphthoic acid and acetic anhydride are mixed in a molar ratio of 1:1 to 1:6 (more preferably 1:2), a catalyst is added, and then the temperature is increased to react under a nitrogen environment; after the reaction is completed, crystals are precipitated, and the second product is obtained after washing and drying; Step 3: Mix the first product and the second product in a weight ratio range of 60:40 to 80:20 (more preferably 73:27), add a catalyst, introduce nitrogen for purging, and heat to react; after the reaction is completed, cool to obtain the naphthylhydroxycarboxylic acid-parahydroxybenzoic acid copolyester.
[0010] In the above raw material composition, preferably, in the process of preparing naphthylhydroxycarboxylic acid-parahydroxybenzoic acid copolyester, the step 1 comprises: adding parahydroxybenzoic acid and acetic anhydride in a molar ratio range of 1:1 to 1:6 (more preferably 1:2) into a reaction container for mixing, and adding 200-400 ppm of a zinc catalyst (which may be a catalyst commonly used in the art, such as zinc-chromium oxide, zinc-aluminum oxide, zinc-aluminum-chromium oxide, zinc-chromium-manganese oxide, zinc-iron oxide, zinc-iron-aluminum oxide, etc.; the same applies hereinafter); heating to a temperature range of 100° C. to 160° C. (more preferably 140° C.) to dissolve parahydroxybenzoic acid and acetic anhydride into a colorless transparent solution, continuously introducing nitrogen to gradually react parahydroxybenzoic acid and acetic anhydride to form an ester, and condensing and refluxing the acetic anhydride for a suitable time before stopping the reaction; pouring the reactants into water, washing and drying the precipitated white crystals to obtain a first product; The step 2 comprises: adding 6-hydroxy-2-naphthoic acid and acetic anhydride in a molar ratio of 1:1 to 1:6 (more preferably 1:2) into a reaction container for mixing, and adding 200-400 ppm of a zinc catalyst; heating to a temperature range of 100° C. to 160° C. (more preferably 140° C.) to dissolve p-hydroxybenzoic acid and acetic anhydride into a colorless transparent solution, continuously introducing nitrogen gas to gradually react p-hydroxybenzoic acid and acetic anhydride to form an ester, and condensing and refluxing the acetic anhydride for a suitable time before stopping the reaction; pouring the reactants into water, washing and drying the precipitated white crystals to obtain a second product; The step three comprises: adding the first product and the second product into a reaction container in a weight ratio of 60:40 to 80:20 (more preferably 73:27) for mixing, adding 200-400 ppm of a zinc catalyst, and passing nitrogen for purging; placing the reaction container in a salt bath, reacting at 247-255° C., heating to 265-280° C., evacuating to a vacuum degree of -0.08 MPa, and simultaneously heating to 280-300° C. and maintaining for 1-1.5 hours, stopping the reaction, and cooling to 100° C. to obtain the naphthylhydroxycarboxylic acid-parahydroxybenzoic acid copolyester.
[0011] In the above raw material composition, preferably, the thermoplastic elastomer is selected from one or a combination of two or more of TPU, TPA and POE.
[0012] In the above raw material composition, preferably, the raw material composition comprises, by parts by mass: PET resin 100 parts; Dispersed phase 0.3~0.75 parts; 5-10 parts of naphthylhydroxycarboxylic acid-parahydroxybenzoic acid copolyester; Thermoplastic elastomer 5~10 parts.
[0013] In the above raw material composition, preferably, the raw material composition further comprises a blowing agent, and the blowing agent is preferably one or a combination of two or more of an inert blowing agent (such as N2, CO2), a hydrocarbon blowing agent (cyclopentane, butane, etc.), and a hydrofluorocarbon blowing agent (HFCs). The amount of the blowing agent can be controlled to be 8% to 15%.
[0014] The present invention also provides a method for preparing high-strength and high-toughness PET foam, wherein the preparation method is prepared using the raw material composition of the high-strength and high-toughness PET foam as raw material; The preparation method comprises the following steps: The PET resin, the dispersed phase, the naphthyl hydroxycarboxylic acid-parahydroxybenzoic acid copolyester and the thermoplastic elastomer are added into an intermeshing co-rotating parallel twin-screw extruder (the first stage of a two-stage continuous extrusion foaming unit) for melt blending, and then supercritical CO2 and cyclopentane are injected into the intermeshing co-rotating parallel twin-screw extruder in a ratio ranging from 1:1 to 5:4 (more preferably 3:2) to obtain a blend melt; The blend melt enters the single-screw extruder (the second stage of the two-stage continuous extrusion foaming unit) through the transition section, cools down, and is extruded and foamed after passing through the mold. The foam is then quickly cooled and shaped by the molding device, thereby obtaining high-strength and high-toughness PET foam.
[0015] In the above preparation method, the meshing co-directional parallel twin-screw extruder and the single-screw extruder are respectively two parts of a two-stage continuous extrusion foaming unit, connected by a transition section in the middle. More preferably, the speed of the twin screws in the first-stage meshing co-directional parallel twin-screw extruder is 200-250 r / min, and the barrel setting temperature is 280-300°C.
[0016] In the above preparation method, preferably, the blend melt is cooled to 245-265° C. in a single screw extruder, and the extrusion pressure is 6-8 MPa.
[0017] In the above preparation method, preferably, the eccentric rotor (i.e., the stretching element) in the meshing co-directional parallel twin-screw extruder is a bilaterally symmetrical structure; The surface of the stretching element is provided with two stretching threads (large lead threads), namely left-handed threads and right-handed threads, and the lead of the left-handed threads and the right-handed threads are both 1 a ~4 a The axial lengths (L1, L2) of the left-handed and right-handed threads of the tensile element are both 0.5 a ~2 a In the same tensile element, the lead of the left-hand thread and the right-hand thread is the same.
[0018] The projection of the stretching thread along the axis of the stretching element is a circle, and the diameter of the circle is a ; The outer contour curves of the stretched thread in all cross sections perpendicular to the axis are the same, and the contour curves are composed of eight arcs, including a first arc, a second arc, a third arc, a fourth arc, a fifth arc, a sixth arc, a seventh arc and an eighth arc connected in sequence; wherein the radius of the first arc is 0.5 a , and the arc corresponds to a central angle of 10°~20°, and the radius of the second arc is 0.1 a ~0.2 a , and the arc corresponds to a central angle of 55°~70°; the radius of the third arc is 0.3 a ~0.5 a , and the arc corresponds to a central angle of 55°~70°; the third arc is tangent to the second arc; the radius of the fourth arc is 0.5 a ~0.7 a , and the arc corresponds to a central angle of 70°~85°; the fourth arc is tangent to the third arc; the fifth arc is centrally symmetrical with the first arc, the sixth arc is centrally symmetrical with the second arc, the seventh arc is centrally symmetrical with the third arc, and the eighth arc is centrally symmetrical with the fourth arc. The fourth arc has the greatest influence on the obtained fiber. At the same time, the lead of the left-handed thread and the right-handed thread also has an important influence on the obtained fiber, which determines the length of the stretching element in the barrel to produce the stretching effect.
[0019] The present invention applies tensile stress to the dispersed phase in PET on a meshing parallel twin-screw extruder by designing a special tensile element, so that the dispersed phase is stretched and thinned to become fibrous. At the same time, multiple convergent flow channels are designed in the extrusion die (i.e., the flow cross-sectional area of PET extrusion flow in the convergent flow channel gradually decreases) to control the PET / dispersed phase to be further subjected to the tensile flow field during the extrusion foaming process, thereby increasing the aspect ratio of the dispersed phase fiber, thereby achieving uniform dispersion of the high specific surface area fiber dispersed phase in the PET foam, and finally preparing a PET / fiber composite foam with ultra-high strength and toughness.
[0020] The present invention also provides a high-strength and high-toughness PET foam, which is prepared by the above method; Preferably, the high-strength and high-toughness PET foam satisfies one or a combination of two or more of the following properties: The foam compression strength is 1.65~1.85MPa; Foam shear strength is 0.75~0.95MPa; The foam shear elongation at break is 10%~20%.
[0021] In the process of melt blending, extrusion and foaming, the present invention applies stretching to the dispersed phase through the eccentric rotor (stretching element) and the convergent flow channel in the mold to form a long fiber structure of the dispersed phase, thereby increasing the bonding force between the dispersed phase and PET, thereby preparing a high-strength and high-toughness PET fiber composite foam.
[0022] The PET foam prepared by the invention has good mechanical properties, especially high compression strength, shear strength and shear elongation at break. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the appearance drawing of the tensile component.
[0024] Figure 2 Relevant parameter diagram of the cross section of the tensile element.
[0025] Figure 3 This is the relevant parameter diagram of the length direction of the tensile element.
[0026] Figure 4 It is a schematic diagram of a two-stage continuous extrusion foaming unit.
[0027] Figure 5 The foam morphology scanning diagrams of Examples 1-2 and Comparative Example 1.
[0028] Figure 6 The quenched cross-sectional morphology of the composites of Examples 5-6 and Comparative Example 3.
[0029] Description of main figures: Twin-screw extruder 1, gas injection machine 2, stretching element 3, transition section 4, single-screw extruder 5, long convergent flow channel in the die 6, short convergent flow channel on the die lip 7, cooling equipment 8, and traction equipment 9. DETAILED DESCRIPTION
[0030] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0031] The raw materials used in the embodiments and comparative examples are as follows: PET, bottle flakes, intrinsic viscosity 0.8dL / g; PBO; TGIC; PHBNA; TPU; POE.
[0032] Among them, PHBNA is synthesized from 6-hydroxy-2-naphthoic acid HNA and p-hydroxybenzoic acid HBA, and the specific synthesis process is as follows: p-Hydroxybenzoic acid and acetic anhydride were added into a three-necked flask at a molar ratio of 1:2, and a certain amount of zinc catalyst (400ppm) was added at the same time; when the temperature reached 140°C, the solid powder gradually dissolved into a colorless transparent solution, and nitrogen was continuously introduced, p-Hydroxybenzoic acid and acetic anhydride gradually reacted to form an ester, and the acetic anhydride was condensed and refluxed for a certain period of time, and then the reaction was stopped; The reactants were poured into a beaker filled with deionized water, and white crystals were precipitated. The white crystals were washed and dried for 24 hours to obtain the first product, which was taken out for later use. The chemical reaction that occurred is as follows:
[0033]
[0034] Separately, 6-hydroxy-2-naphthoic acid is reacted with acetic anhydride in the same process as above to obtain the second product. The chemical reaction is as follows:
[0035]
[0036] The first product and the second product are co-melted and polymerized: a certain weight is weighed, and the first product and the second product are placed in a three-necked flask at a mass ratio of 73:27, and a certain ratio of zinc catalyst (based on the total weight of the monomer, 400ppm) is added; nitrogen is purged to remove the air in the system; then the reaction bottle is placed in a salt bath, and the temperature is raised to 280°C after the reaction at 250°C, and the temperature is raised while vacuuming and maintained for 1h; the reaction is stopped and the product PHBNA is taken out after cooling to 100°C. The chemical reaction that occurs is as follows:
[0037]
[0038] The foams of Examples 1-4 and Comparative Examples 1-2 were prepared using a two-stage continuous extrusion foaming unit (eg Figure 4 As shown in the figure, the two-stage continuous extrusion foaming unit comprises a twin-screw extruder 1 and a single-screw extruder 5, which are connected by a transition section 4, wherein the twin-screw extruder 1 is connected to a gas injection machine 2 and is provided with a stretching element 3 inside, and the outlet of the single-screw extruder 5 is sequentially connected to a long convergent flow channel 6 in the die, a short convergent flow channel 7 on the die lip, a cooling device 8, and a traction device 9; The preparation process of the foams of Examples 1-4 and Comparative Examples 1-2 includes: PET and PHBNA were dried in a vacuum oven at 160°C for 6 h, and PBO, TGIC, TPU and POE were dried in a blast oven at 60°C for 6 h. The dried PET, PBO, TGIC, PHBNA, TPU and POE were added to the twin-screw extruder 1 of the extrusion foaming unit for melt blending. After the polymers were fully melt blended, the supercritical CO2-cyclopentane mixture was injected into the twin-screw extruder 1 at a ratio of 3:2, wherein the speed of the twin-screw extruder 1 was 200-250 r / min, and the temperature of the melt blending was 280-300°C; The blend melt enters the single screw extruder 5, and the temperature is reduced to 245-265° C. in the single screw extruder 5, and the extrusion pressure is maintained at 6-8 MPa; The blend melt is passed through a secondary convergence die at high speed for extrusion and foaming, and the foam is quickly cooled and shaped.
[0039] Among them, Examples 1-2 and Comparative Example 1 were processed using stretching elements, and Examples 3-4 and Comparative Example 2 were processed using conventional screw elements.
[0040] The structures of the stretching elements used in Examples 1-2 and Comparative Example 1 are as follows: Figure 1 , Figure 2 , Figure 3 As shown, the stretching element is a bilaterally symmetrical structure; The surface of the tensile element is provided with two sections of tensile threads (large lead threads), namely left-handed threads and right-handed threads; the lead of the left-handed threads and the right-handed threads of the tensile element are both 3 a ; The axial length of the tensile element is 3 a , that is, the axial length L1 of the left-hand thread and the axial length L2 of the right-hand thread are 1.5a respectively; The projection of the stretching thread along the axis of the stretching element is a circle, and the diameter of the circle is a =32mm; The cross-sectional profile curve of the stretched thread at any position of the axis is the same, and the profile curve includes a first arc, a second arc, a third arc, a fourth arc, a fifth arc, a sixth arc, a seventh arc and an eighth arc connected in sequence, wherein the radius of the first arc is 0.5 a (16 mm), and the arc corresponds to a central angle of 20°; the radius of the second arc is 0.155 a (5 mm), and the arc corresponds to a central angle of 65°; the radius of the third arc is 0.4 a (12.8 mm), and the arc corresponds to a central angle of 65°; the radius of the fourth arc is 0.55 a(17.6 mm), and the arc corresponds to a central angle of 82°. The fifth arc is centrally symmetrical with the first arc, the sixth arc is centrally symmetrical with the second arc, the seventh arc is centrally symmetrical with the third arc, and the eighth arc is centrally symmetrical with the fourth arc; wherein, Figure 2 As shown, the first arc is the arc between points A and B, the second arc is the arc between points B and C, the third arc is the arc between points C and D, the fourth arc is the arc between points D and E, the fifth arc is the arc between points E and F, the sixth arc is the arc between points F and G, the seventh arc is the arc between points G and H, and the eighth arc is the arc between points H and A.
[0041] The contents (mass fractions) of the components of Examples 1-4 and Comparative Examples 1-2 are shown in Table 1.
[0042] Table 1:
[0043]
[0044] The expansion ratio of the PET foam in Examples 1-4 and Comparative Examples 1-2 was 10 times.
[0045] The compression performance test of Examples 1-4 and Comparative Examples 1-2 was performed with reference to the standard IOS 844. The foam compression strengths of Comparative Example 1, Example 1 and Example 2 were 1.77 MPa, 2.24 MPa and 2.45 MPa, respectively; the foam compression strengths of Comparative Example 2, Example 3 and Example 4 were 0.79 MPa, 1.26 MPa and 1.33 MPa, respectively; the foam shear strengths of Comparative Example 1, Example 1 and Example 2 were 0.37 MPa, 1.18 MPa and 1.36 MPa, respectively; the foam shear strengths of Comparative Example 2, Example 3 and Example 4 were 0.07 MPa, 0.35 MPa and 0.66 MPa, respectively; the foam shear fracture elongations of Comparative Example 1, Example 1 and Example 2 were 5.75%, 10.19% and 12.00%, respectively; the foam shear fracture elongations of Comparative Example 2, Example 3 and Example 4 were 3.47%, 7.04% and 9.12%, respectively.
[0046] According to the above test results, it can be seen that by comparing Example 1 with Comparative Example 1, when the amount of PHBNA added is 5 parts, the compressive strength of the PET foam can be increased by 26%, the shear strength can be increased by 2.18 times, and the shear elongation at break can be increased by 77%; By comparing Example 2 with Comparative Example 1, when the addition amount of PHBNA is 10 parts, the compressive strength of the PET foam can be increased by 38%, the shear strength can be increased by 2.67 times, and the shear elongation at break can be increased by 108%.
[0047] By comparing Examples 3 and 4 with Comparative Example 2, the toughness of the foam is significantly improved.
[0048] The foam morphologies of Examples 1-2 and Comparative Example 1 were observed using a scanning electron microscope. Figure 5 As shown. Figure 5 From the cell morphology, cell size and cell density, it can be seen that PHBNA has no significant effect on the foaming behavior of PET. Therefore, it is judged that the main factor affecting the mechanical properties of foam is fiber.
[0049] In order to better observe the fibers and judge the function of the fibers, the PET foams in Examples 1-2 and Comparative Example 1 were crushed and then subjected to compression molding to eliminate the bubbles (the compression molding temperature was 265°C and the pressure was 5 MPa), and Examples 5-6 and Comparative Example 3 were prepared, as shown in Table 2. The quenched cross-sectional morphologies of the composites of Examples 5-6 and Comparative Example 3 were observed by scanning electron microscopy, as shown in Table 2. Figure 6 As shown. Figure 6 It can be seen that during the melt blending process, PHBNA is oriented in PET to form a rod-like fiber morphology.
[0050] Table 2:
[0051]
[0052] The PET composite materials in Examples 5-6 and Comparative Example 3 were injection molded into specimens using an injection molding machine and then subjected to mechanical property testing. The tensile property test determination standard was based on ISO 527. The test results are shown in Table 3.
[0053] Table 3:
[0054]
[0055] According to the test results shown in Table 3, it can be seen that when the amount of PHBNA added is 10 parts, the tensile strength of the PET composite material can be increased by 17% by comparing Example 6 with Comparative Example 3. Therefore, by applying stretching to the dispersed phase through the eccentric rotor and the secondary convergence die to form a long fiber structure of the dispersed phase, a high-strength PET fiber composite foam can be prepared.
Claims
1. A raw material composition of high-strength and high-toughness PET foam, characterized in that: The raw material composition of the high-strength and high-toughness PET foam comprises, by parts by mass: PET resin 100 parts; Dispersed phase 0.3~0.75 parts; Naphthalene hydroxycarboxylic acid-parahydroxybenzoic acid copolyester less than 10 parts; Thermoplastic elastomer 10 parts or less.
2. The raw material composition of high-strength and high-toughness PET foam according to claim 1, characterized in that: The dispersed phase is selected from one or a combination of two or more of 2,2'-(1,3-phenylene)-bisoxazoline, pyromellitic anhydride and triglycidyl isocyanurate.
3. The raw material composition of high-strength and high-toughness PET foam according to claim 1, characterized in that: The naphthyl hydroxycarboxylic acid-parahydroxybenzoic acid copolyester is prepared by the following steps: Step 1: p-hydroxybenzoic acid and acetic anhydride are mixed in a molar ratio of 1:1-1:6, a catalyst is added, and then the temperature is increased to react under a nitrogen environment; after the reaction is completed, crystals are precipitated, and the first product is obtained after washing and drying; Step 2: 6-hydroxy-2-naphthoic acid and acetic anhydride are mixed in a molar ratio of 1:1-1:6, a catalyst is added, and then the temperature is increased to react under a nitrogen environment; after the reaction is completed, crystals are precipitated, and the second product is obtained after washing and drying; Step 3: Mix the first product and the second product in a weight ratio of 60:40 to 80:20, add a catalyst, introduce nitrogen for purging, and heat to react; after the reaction is completed, cool to obtain the naphthylhydroxycarboxylic acid-parahydroxybenzoic acid copolyester.
4. The raw material composition of high-strength and high-toughness PET foam according to claim 3, characterized in that: The step 1 comprises: adding p-hydroxybenzoic acid and acetic anhydride in a molar ratio of 1:1-1:6 into a reaction container for mixing, and adding 200-400 ppm of a zinc catalyst at the same time; raising the temperature to 140° C. to dissolve the p-hydroxybenzoic acid and acetic anhydride into a colorless transparent solution, continuously introducing nitrogen gas to gradually react the p-hydroxybenzoic acid and acetic anhydride to form an ester, and stopping the reaction after condensing and refluxing the acetic anhydride for a suitable time; pouring the reactants into water, washing and drying the precipitated white crystals, and obtaining a first product; The step 2 comprises: adding 6-hydroxy-2-naphthoic acid and acetic anhydride in a molar ratio of 1:1-1:6 into a reaction container for mixing, and adding 200-400 ppm of a zinc catalyst at the same time; raising the temperature to 140° C. to dissolve p-hydroxybenzoic acid and acetic anhydride into a colorless transparent solution, continuously introducing nitrogen gas to gradually react p-hydroxybenzoic acid and acetic anhydride to form an ester, and condensing and refluxing the acetic anhydride for a suitable time before stopping the reaction; pouring the reactants into water, washing and drying the precipitated white crystals to obtain a second product; The step three comprises: adding the first product and the second product into a reaction container at a weight ratio of 60:40 to 80:20 for mixing, adding 200-400 ppm of a zinc catalyst, and passing nitrogen for purging; placing the reaction container in a salt bath, reacting at 247-255° C., heating up to 280° C., evacuating to a vacuum degree of -0.08 MPa, and simultaneously heating up and maintaining for 1-1.5 hours, stopping the reaction, and cooling to 100° C. to obtain the naphthylhydroxycarboxylic acid-parahydroxybenzoic acid copolyester.
5. The raw material composition of high-strength and high-toughness PET foam according to claim 1, characterized in that: The thermoplastic elastomer is selected from one or a combination of two or more of TPU, TPA and POE.
6. The raw material composition of high-strength and high-toughness PET foam according to claim 1, characterized in that: The raw material composition of the high-strength and high-toughness PET foam comprises, by parts by mass: PET resin 100 parts; Dispersed phase 0.3~0.75 parts; 5-10 parts of naphthylhydroxycarboxylic acid-parahydroxybenzoic acid copolyester; Thermoplastic elastomer 5~10 parts.
7. A method for preparing high-strength and high-toughness PET foam, characterized in that: The preparation method is prepared using the raw material composition of the high-strength and high-toughness PET foam described in any one of claims 1 to 6 as raw material; The preparation method comprises the following steps: The PET resin, the dispersed phase, the naphthyl hydroxycarboxylic acid-parahydroxybenzoic acid copolyester and the thermoplastic elastomer are added into an intermeshing co-rotating parallel twin-screw extruder for melt blending, and then supercritical CO2 and cyclopentane are injected into the intermeshing co-rotating parallel twin-screw extruder in a ratio of 1:1 to 5:4 to obtain a blend melt; The blend melt enters a single-screw extruder, is cooled, and is extruded and foamed after passing through a mold at high speed. The foam is quickly cooled and shaped to obtain a high-strength and high-toughness PET foam.
8. The method for preparing high-strength and high-toughness PET foam according to claim 7, characterized in that: The twin screws in the meshing co-rotating parallel twin screw extruder have a rotation speed of 200-250 r / min and a temperature of 280-300° C.; And / or, the blend melt is cooled to 245-265° C. in the single screw extruder, and the extrusion pressure is 6-8 MPa.
9. The method for preparing high-strength and high-toughness PET foam according to claim 7, characterized in that: The stretching element in the meshing parallel twin-screw extruder is a bilaterally symmetrical structure; The surface of the tensile element is provided with two sections of tensile threads, namely, a left-handed thread and a right-handed thread, and the lead of the left-handed thread and the right-handed thread are both 1a~4a; the axial length of the left-handed thread and the right-handed thread of the tensile element are both 0.5a~2a; The projection of the stretching thread along the axial direction of the stretching element is a circle, and the diameter of the circle is a; The outer contour curves of the stretched thread in all cross sections perpendicular to the axis are the same, and the contour curves are composed of eight arcs, including a first arc, a second arc, a third arc, a fourth arc, a fifth arc, a sixth arc, a seventh arc and an eighth arc connected in sequence; wherein, the radius of the first arc is 0.5a, and the arc corresponds to a central angle of 10°~20°, the radius of the second arc is 0.1a~0.2a, and the arc corresponds to a central angle of 55°~70°; the radius of the third arc is 0.3a~0.5a, and the arc corresponds to a central angle of 55°~70°; the third arc is tangent to the second arc; the radius of the fourth arc is 0.5a~0.7a, and the arc corresponds to a central angle of 70°~85°; the fourth arc is tangent to the third arc; the fifth arc is centrally symmetrical with the first arc, the sixth arc is centrally symmetrical with the second arc, the seventh arc is centrally symmetrical with the third arc, and the eighth arc is centrally symmetrical with the fourth arc.
10. A high-strength and high-toughness PET foam, characterized in that: The high-strength and high-toughness PET foam is prepared by the preparation method of the high-strength and high-toughness PET foam according to any one of claims 7 to 9; The high-strength and high-toughness PET foam meets one or a combination of two or more of the following properties: The foam compression strength is 1.65~1.85MPa; Foam shear strength is 0.75~0.95MPa; The foam shear elongation at break is 10%~20%.
Citation Information
Patent Citations
Method for preparing in-situ micro fiber blend in direct extrusion mode
CN106003460A
Polyethylene glycol terephthalate foam material as well as preparation method and application thereof
CN115160746A
Wheel-shaped stretching screw for double-screw extruder and meshing method
CN116175931A
Supercritical extrusion liquid crystal fiber reinforced PET (Polyethylene Terephthalate) foam and preparation process thereof
CN119192654A
Manufacture of thermoplastic resin foam
JP2000117805A
Cited By
High-strength, high-toughness pet foam, raw material composition therefor, and preparation method therefor
WO2026144224A1